Research on 5G-TSN joint scheduling mechanism based on radio channel information - Lei SUN; Jianquan WANG; Shangjing LIN; Zhangchao MA; Wei LI; Liang Qilian; Rong HUANG (Tongxin xuebao)
To solve the deterministic transmission problem of periodic and time-triggered industrial traffics in wireless environment， a joint optimization mechanism of 5G and time sensitive networking based on radio channel information was considered.Based on improved traffic process architecture in time sensitive network， the traffics bearing on radio channel with worse quality could be processed in priority.In 5G networks， the relationship among radio channel quality， resource numbers and the maximum transmission times over radio was modeled， and the maximum transmission times satisfied data transmission reliable probability could be computed from the model，then the transmission time budget in 5G system for multiple industrial traffics bearing on diverse radio resources could be adjusted dynamically by retransmission factors.Simulation results demonstrate that the proposed joint scheduling mechanism achieves less TSN transmission delay of industrial traffics bearing on worse quality radio resources and can eliminate jitter caused by retransmission due to variation of 5G radio channel， which can guarantee end-to-end deterministic delay for industrial traffics.